2015
DOI: 10.1136/bmjquality.u207268.w2918
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of discharge summaries: implementing updated Academy of Medical Royal Colleges standards at a district general hospital

Abstract: Quality of documentation is harder to quantify and incentivise, but it has a significant impact on patient care. Good discharge summaries facilitate continuity between secondary and primary care.The junior doctors’ forum led this project to improve the quality of electronic discharge summaries (eDS). Baseline measurement revealed significant room for improvement. We measured the quality of 10 summaries per month (across all inpatient specialties), against 23 indicators from the revised Academy of Medical Royal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…39 Strategies such as the use of optimised electronic discharge summaries and automated clinician prompting may improve discharge summary rates, along with auditing and the use of quality assessment tools. [40][41][42] The strengths of the present study include the temporal and clinical trends revealed from an analysis of almost 745 000 ED presentations made by metropolitan Melbourne's older population over a period of 5 years. A limitation of the study is that the AIHW definition used to identify PAGP-type ED presentations has been criticised for overestimating presentations, particularly in older patients, where using triage category as a proxy for urgency and resource requirement can be misleading.…”
mentioning
confidence: 99%
“…39 Strategies such as the use of optimised electronic discharge summaries and automated clinician prompting may improve discharge summary rates, along with auditing and the use of quality assessment tools. [40][41][42] The strengths of the present study include the temporal and clinical trends revealed from an analysis of almost 745 000 ED presentations made by metropolitan Melbourne's older population over a period of 5 years. A limitation of the study is that the AIHW definition used to identify PAGP-type ED presentations has been criticised for overestimating presentations, particularly in older patients, where using triage category as a proxy for urgency and resource requirement can be misleading.…”
mentioning
confidence: 99%
“…Thus, courses in the medical curriculums that cover (correct) writing of medical DS are likely to raise the overall quality of DS. Feedback on written DS, the use of checklists and other well‐designed digital solutions may improve communication and have been shown to be successful methods in improving DS writing 37‐42 …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, national standards have been introduced in some countries with the aim of improving and standardising the content of discharge summaries [ 28 – 30 ]. Such standards can improve the quality of communication at discharge, but audits have shown variable adherence to recommendations [ 31 , 32 ].…”
Section: Can Improving Continuity Of Care At Hospital Discharge Impromentioning
confidence: 99%